Assessing strategic, tactical and operational alignment factors for SMEs: alignment across the organisation's value chain. (28th December 2007) - Gutierrez, Anabel; Serrano, Alan
Strategic alignment approaches aim to improve organisational performance, enhance efficiency and maintain or gain competitive advantage. The majority of assessment alignment approaches, however, target the strategic level and overlook the tactical and operational levels. Furthermore, most of the approaches have been tested in large organisations and little research has been conducted to investigate their effectiveness in Small and Medium Enterprises (SMEs). This paper proposes an assessment instrument that aims to understand alignment at all three levels and which has been piloted through an SME case study. The results suggest that this instrument is useful for (a) sharing the knowledge needed to achieve alignment between participants at all three levels, (b) identifying the areas where alignment strategies are weak and need further improvement, (c) identifying those areas where there is conflict between strategic, tactical and operational levels, and (d) addressing SME needs.